Density functional theory study on the reaction of triazol-3-one with nitronium: direct nitration versus acidic group-induced nitration1. Issue 32 (10th April 2015) - Wang, Kuan; Chen, Jian-Gang; Wang, Bozhou; Liu, Fengyi; Liu, Zhao-Tie; Liu, Zhong-Wen; Wang, Wenliang; Jiang, Jinqiang; Hao, Zhengping; Lu, Jian
<x xml:space="preserve">Abstract</x> Herein, an unexpected induction effect derived from the coexisted acid group (NO3− and/or HSO4−) was proposed. The impact of the induction effect and the resulted enhanced catalytic effect on the nitration of TO was systematically demonstrated.